Pemanfaatan Ekstrak Kulit Ubi Jalar Ungu (Ipomea batatas L.) sebagai Bahan Pewarna Alternatif untuk Pengamatan Mikroskopis Paramecium sp. dalam Pembelajaran Biologi - Fatimatuzahro, Dewi; Tyas, Dian Ayuning; Hidayat, Saifullah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Purple sweet potato (Ipomea batatas L.) is a tuber that has purple meat and skin. The purple color of purple sweet potato is usually used by the community as a food coloring, while the sweet potato skin is considered only waste and disposed of. This study aims to determine whether purple sweet potato skin extract can be used as an alternative dye on microscopic observations of Paramecium sp. The research used experimental approach with post test only control group design. The process of purple sweet potato skin extraction using chemical solvents is ethanol, acetic acid and water. The extractions with three treatments were A, B, and C respectively different ratios (25: 1: 5), (15: 1: 15) and (5: 1:25). The results of microscopic observations quantitatively analyzed using Anova One Way test obtained sign. > 0.05 which means the purple sweet potato skin extraction results can be used as an alternative dye for microscopic observation of Paramecium sp. Qualitative analysis of the results of observations in which treatment A shows the best dye results in coloring Paramecium sp.